Innovation and the performance of Portuguese businesses: a ‘SURE’ approach - Marques, Carla (2013)
There is a general consensus that in a competitive business environment, firms’ performance will depend on their capacity to innovate. To clarifying how, when and to what extent innovation affects the market and financial performance of firms, the authors deploy seemingly unrelated regression equation model to examine innovation in over 500 Portuguese firms from 1998 to 2004. The results confirm, as theorists have frequently assumed, that innovation positively affects firms’ performance; but they also suggest that the reverse is true, a result that is less intuitively obvious, given the complexity of the innovation process and local, national and global competitive environments.